Acetazolamide as an Alternative to Standard Diuretics in Acute Heart Failure: A Randomized Study in STEMI Patients Undergoing PCI - Algutaini, Safana Abdullah; Alghazi, Ebaa (Journal of Medical Health Research and Psychiatry, 2024)
Background: Objective: This study evaluated the efficacy and safety of Acetazolamide as a diuretic and fluid retention reliever in patients with acute heart failure due to ST-Elevation Myocardial Infarction (STEMI) undergoing Percutaneous Coronary Intervention (PCI). The aim was to assess whether Acetazolamide could serve as a viable alternative to traditional diuretics, enhancing fluid management with minimal renal impact. Methods: A randomized, prospective study was conducted with 30 adult STEMI patients undergoing PCI. Participants were evenly divided into two groups: One receiving Acetazolamide (250 mg once) and a control group. Key outcomes included cumulative urine output in the first 12 hours post-admission, changes in serum creatinine levels before and after PCI, and the length of hospital stay. Secondary analyses compared outcomes between patients with and without congestion. Results: Patients receiving Acetazolamide demonstrated significantly higher mean urine output (2368 ± 1768.9 mL) compared to controls (1436.7 ± 926.7 mL), trending toward statistical significance (p = 0.085). Acetazolamide preserved renal function, with serum creatinine decreasing from 1.17 ± 0.05 mg/dL pre-PCI to 1.06 ± 0.04 mg/dL post-PCI (p = 0.009). Hospital stay duration showed a trend toward reduction (4.07 ± 0.26 days vs. 4.60 ± 1.72 days, p = 0.255). Conclusion: Acetazolamide appears effective and safe in improving diuresis and preserving renal function in STEMI patients undergoing PCI, warranting further investigation in larger trials.